Benign Neglect of Anomalous Insertion of the Anterior Horn of the Medial Meniscus as an Incidental Finding During Knee Arthroscopy - Masaki Nagashima, M.D., Ph.D; Toshiro Otani, M.D., Ph.D; Kenichiro Takeshima, M.D., Ph.D; Hiroyuki Seki, M.D., Ph.D; Ken Ishii, M.D., Ph.D (Elsevier, 2020)
Purpose: To evaluate the clinical results following arthroscopic surgery in patients with anomaly of the anterior horn of the medial meniscus (AHMM) that was found unexpectedly during surgery and discuss whether resection is necessary in patients without anteromedial knee pain (AMKP). Methods: Between May 2014 and April 2017, a total of 387 knee arthroscopies in 379 patients were performed. Among these, 11 knees in 11 patients showed an anomalous insertion of the AHMM (incidence, 2.8%), and all 11 patients were included in this study. For these 11 patients, medical records including preoperative diagnosis, arthroscopic findings, and pre- and postoperative clinical evaluations were analyzed. Results: None of the patients complained of AMKP before arthroscopy. Two patients were diagnosed with lateral meniscus injury and the other 9 patients were diagnosed with medial meniscus injury. All anomalies of the AHMM were found incidentally during arthroscopic surgery. The anomaly formed a band-like structure arising from the anterior portion of the medial meniscus and was attached to the anterior aspect of the ACL and femoral intercondylar notch. All 11 patients underwent partial meniscectomy, but anomalies of the AHMM were not resected. One patient was excluded from clinical evaluation, as that patient required subsequent total knee arthroplasty due to osteoarthritis. For the other 10 patients, mean follow-up was 36.8 months (range, 26-61 months). Knee pain was relieved, and none developed postoperative AMKP. Mean Lysholm score improved significantly from 55.9 to 91.2 (P < .001). Conclusions: The incidence of the anomaly was 2.8% in our study. If the patient has no AMKP before arthroscopic surgery, anomaly of the AHMM is a silent lesion that does not warrant resection. Level of Evidence: Level IV, therapeutic case series